Functional characteristics associated with hip abductor torque in severe hip osteoarthritis. (October 2021) - Kawano, Takumi; Nankaku, Manabu; Murao, Masanobu; Goto, Koji; Kuroda, Yutaka; Kawai, Toshiyuki; Ikeguchi, Ryosuke; Matsuda, Shuichi
Abstract: Background: Hip abductor weakness due to the progression of hip osteoarthritis (OA) commonly causes poor functional mobility. The hip abductor strength has also been identified as a clinically relevant factor for successful functional outcomes after total hip arthroplasty. Objectives: This study aimed to examine the functional characteristics related to hip abductor torque in patients with hip OA. Design: A cross-sectional survey study. Methods: One hundred and eight female patients with severe unilateral hip OA participated in this study. Hip abductor torque and pain were measured. The muscle cross-sectional area (CSA) and skeletal muscle density (SMD) of the gluteal muscles were also measured using computed tomography. To identify the hip parameters associated with hip abductor torque, multiple regression analysis was performed. The healthy model included the CSA and SMD of gluteus maximus, gluteus medius, and gluteus minimus; range of motion in hip abduction; age; and body mass index. The affected model included hip pain in addition to the healthy model. Results: In the affected limb, multiple regression analysis identified pain and angle of hip abduction as factors that determine hip abductor torque (Adjusted R 2  = 0.39). In contrast, our analysis identified CSA and SMD of the gluteus medius and SMD of the gluteus minimus as the significant variables related to hip abductor torque in the healthy limb (Adjusted R 2  = 0.40). Conclusion: The findings of this study indicated that it is necessary to consider that hip pain may inhibit muscle exertion and contraction while training to improve the hip abductor torque in the affected limb. Highlights: We investigated factors related to abductor torque of hip osteoarthritis. Hip abductor torque in affected side depends on pain and joint mobility. Hip muscles in healthy limb are the key determinant of abductor torque.